Evaluation of Chitosan Hydrogel for Sustained Delivery of VEGF for Odontogenic Differentiation of Dental Pulp Stem Cells - Si Wu; Yachuan Zhou; Yi Yu; Xin Zhou; Wei Du; Mian Wan; Yi Fan; Xuedong Zhou; Xin Xu; Liwei Zheng (Stem Cells International)
The pulpotomy with pulp capping is aimed at retaining vital pulp with reparative dentin formation. Vascular endothelial growth factor (VEGF) plays a crucial role in dentin regeneration; however, its constant administrations in the human body is still problematic. Chitosan was widely studied as an effective carrier to deliver bioactive molecules in regenerative medicine. In this study, we conducted a chitosan/β-glycerophosphate (CS/β-GP) hydrogel as a VEGF-sustained release system and explored its effects on dental pulp stem cells (DPSCs). CS/β-GP hydrogel was manufactured using a sol-gel method. SEM assay showed the spongy and porous microstructure of the lyophilized hydrogels. DPSCs cultured in the CS/β-GP hydrogel kept adhesion and vitality. CCK-8 assay tested the promoted proliferation activity of DPSCs on the hydrogel. Besides, the added VEGF protein could continually release from VEGF/CS/β-GP hydrogel. The VEGF/CS/β-GP hydrogel could promote the odontogenic differentiation of DPSCs better than VEGF treatment without hydrogel. Our results suggested that CS/β-GP hydrogel could continually release VEGF and contribute to odontogenic differentiation of DPSCs, thus may become a potential carrier of bioactive molecules in pulp capping therapy.